PENERAPAN METODE STORY READING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5 - 6 TAHUN DI TK MELATI / ABA 005 PULAU BALAI - Hasnidar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This study aims to improve speaking skills of children aged 5-6 through methods Story Reading in TK Melati/ ABA 005 Pulau Balai. The method used is a Class Action Research. Class actions that researchers do the research is to use the method Story Reading to improve speaking skills of children aged 5-6 years in TK Melati/ ABA 005 Pulau Balai, and is observed by the observer. Samples taken are TK Melati/ ABA 005 Pulau Balai with the number of children of 20 people, consisting of 13 men and 7 women. Data collection techniques in this research is through observation of teachers and children as well as data capability speaking children aged 5-6 years with use of methods Story Reading. Hipotesis in this study is if the method will be applicable Story Reading can improve speaking skills of children aged 5-6 years in TK Melati/ ABA Pulau Balai 005 can be enhanced through storytelling. Results of the research data obtained by using the method Story Reading can improve the ability to speak of children aged 5-6 years in TK Melati/ ABA 005 Pulau Balai. The percentage increase in the ability to speak the child at the age of 5-6 years using Story Reading methods in TK Melati/ ABA 005 Pulau Balai, from initial data to the second cycle increased by 32.2%. The implication of this study is the use of methods Story Reading used properly, can improve speaking skills of children aged 5-6 years in TK Melati/ ABA 005 Pulau Balai.